Technical efficiency of public hospitals in east Africa: a systematic review and meta-analysis - Anteneh Lamesgen; Bekalu Endalew; Aysheshim Belaineh Haimanot; Tigabu Kidie Tesfie; Elyas Melaku Mazengia; Mulat Belay Simegn; Werkneh Melkie Tilahun; Molla Yigzaw Birhanu; Lakew Asmare; Habtamu Geremew; Muluye Gebrie Mengie (BMC Health Services Research)
Abstract Background Hospitals usually encounter human, capital, and financial resource constraints which alerts the efficient use of allocated resources more than ever. Health system managers are required to identify inefficient hospitals and the drivers of the inefficiencies. Although there are multiple studies examining the efficiency of public hospitals in East Africa, their findings are often variable and inconsistent. Therefore, this study aimed to review published articles on technical efficiency of public hospitals in East African countries. Methods A systematic search of published articles on the technical efficiency of public hospitals was employed using Pubmed, Cochrane library, and google scholar and thirteen studies were included to this review. The studies were described in terms of their publication year, sample size, inputs and outputs used in the efficiency analysis, and the technical efficiency levels. Finally, we assessed their quality and estimate the mean technical efficiency using meta-analysis. Results The technical efficiency score of public hospitals varied across countries in east Africa which ranged from 0.64 ± 0.34 in Tanzania to 0.99 ± 0.03 in Ethiopia. The mean technical efficiency was 0.82 (95% CI = 0.56, 1.07) for primary hospitals and 0.88 (95% CI = 0.82, 0.95) for secondary level hospitals. Technical efficiency of public hospitals was negatively correlated with the number of hospitals (the sample size) and positively correlated with the number of inputs and outputs included in the efficiency analysis. Conclusions This review revealed that the technical efficiency of public hospitals in east Africa requires an improvement. To enable effective and efficient hospital management and improvement in hospital efficiency, health managers and policymakers must identify the drivers of hospital inefficiency. Systematic reviews on public hospital efficiency, which are currently rare in Africa, should be conducted on a much larger scale in order to create more, and validated information for use in policy-making. Trial registration This review protocol was registered and approved by the international prospective register of systematic reviews with a Protocol ID: CRD42023444729.